Teaching Style of Christian Religious Educators at SMA Negeri Palangka Raya - Saputra, Robi; Ginting, Matius Timan Herdi; Pongoh, Fernando Dorothius (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research focuses on analyzing the teaching style of Christian Religious Education (PAK) teachers at SMA Negeri Palangka Raya to understand its influence on students' interest and motivation to learn. Using a qualitative approach, data were collected through interviews with one PAK teacher and twenty Grade XI students from May to September 2024. The results showed that PAK teachers have implemented technological, personalized, and interactional teaching styles with indicators in the form of learning materials, material delivery processes, and student and teacher roles. However, the classical teaching style was not fully implemented because it is not based on students' interests. In addition, it was found that variations in teaching aspects such as variations in voice, contact, movement, and interaction can increase students' motivation to learn. This study recommends that schools and teachers continue to improve the effectiveness of teaching styles by considering students' needs and characters.